Drifting away from religion? A perspective from German teacher education - Domsel, Maike Maria (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2022)
Due to the dynamic situations in Germany and other Western European countries, the break with religious traditions has been already completely achieved and a far-reaching spiritual-religious plurality has been formed. Against this backdrop of a multitude, in part contradictory, spiritual signs of the times, even prospective teachers of religion can no longer assume an already established and reflected spiritual-religious identity. The following article indeed will deeply explore and interpret personal and professional experiences through self-reflection and writing and relate these, for example, to religious, cultural, and social implications. In addition, it will reflect more closely the field of tension between pluralistic-secular life-world and (Christian)-religious traditions in which prospective teachers of religion find themselves and present a time-sensitive and addressee-oriented spirituality module supporting them in establishing their own spiritual-religious identity. It is hoped that this sustainable and communicable model serves to enable teachers of religion to communicate about it (with pupils) and to meet others’ religious identities in an open and empathetic way.